Inhibitory and toxic effects of extracellular self‐DNA in litter: a mechanism for negative plant–soil feedbacks?. Issue 3 (29th October 2014) - Mazzoleni, Stefano; Bonanomi, Giuliano; Incerti, Guido; Chiusano, Maria Luisa; Termolino, Pasquale; Mingo, Antonio; Senatore, Mauro; Giannino, Francesco; Cartenì, Fabrizio; Rietkerk, Max; Lanzotti, Virginia
Summary Plant–soil negative feedback (NF) is recognized as an important factor affecting plant communities. The objectives of this work were to assess the effects of litter phytotoxicity and autotoxicity on root proliferation, and to test the hypothesis that DNA is a driver of litter autotoxicity and plant–soil NF. The inhibitory effect of decomposed litter was studied in different bioassays. Litter biochemical changes were evaluated with nuclear magnetic resonance (NMR) spectroscopy. DNA accumulation in litter and soil was measured and DNA toxicity was assessed in laboratory experiments. Undecomposed litter caused nonspecific inhibition of root growth, while autotoxicity was produced by aged litter. The addition of activated carbon (AC) removed phytotoxicity, but was ineffective against autotoxicity. Phytotoxicity was related to known labile allelopathic compounds. Restricted 13C NMR signals related to nucleic acids were the only ones negatively correlated with root growth on conspecific substrates. DNA accumulation was observed in both litter decomposition and soil history experiments. Extracted total DNA showed evident species‐specific toxicity. Results indicate a general occurrence of litter autotoxicity related to the exposure to fragmented self‐DNA. The evidence also suggests the involvement of accumulated extracellular DNA in plant–soil NF. Further studies are needed to further investigate this unexpected function of extracellular DNA at the ecosystem level and related cellular and molecular mechanisms.